2021
DOI: 10.1101/2021.03.12.435217
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Embryo Lethality Assay for Evaluating Virulence of Isolates from Bacterial Chondronecrosis with Osteomyelitis in Broilers

Abstract: We used an embryo lethality assay (ELA) to assess virulence for different isolates from cases of bacterial chondronecrosis with osteomyelitis (BCO) in broilers. ELA has been used to measure virulence and lethal dosage of Enterococcus faecalis and Enterococcus cecorum. We hypothesized that ELA could substitute for more laborious and costly assessments of BCO isolate pathogenicity using live birds. We evaluated two different levels of bacteria injected into eggs from layer and commercial broiler embryos. Signifi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…Nevertheless, it has been recently discussed whether embryo lethality assays are reliable tools to determine EC pathogenicity. In a recent study, an EC strain isolated from severe bone lesions had low pathogenicity in an embryo lethality assay, leading to the conclusion that those assays are not the most representative measures to determine EC pathogenicity [28]. Our findings strengthen this hypothesis.…”
Section: Plos Onesupporting
confidence: 77%
See 1 more Smart Citation
“…Nevertheless, it has been recently discussed whether embryo lethality assays are reliable tools to determine EC pathogenicity. In a recent study, an EC strain isolated from severe bone lesions had low pathogenicity in an embryo lethality assay, leading to the conclusion that those assays are not the most representative measures to determine EC pathogenicity [28]. Our findings strengthen this hypothesis.…”
Section: Plos Onesupporting
confidence: 77%
“…Embryo lethality assays have also been used to characterize the virulence of EC strains. Extraintestinal EC isolates seem to cause higher embryo lethality rates and are therefore thought to be more virulent than intestinal strains [21,[26][27][28]. Nonetheless, until now, there is no experimental evidence that some strains are more virulent than others in broiler chicks in the first weeks of life.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that the causative agents of lameness due to bacterial chondronecrosis and osteomyelitis lesions can significantly differ in specific farms. Moreover, genotyping demonstrated that the genomes of S. aureus in this study were significantly related to isolates obtained from European chickens (25).…”
Section: Lameness Due To Staphylococcus Aureus Infectionmentioning
confidence: 61%
“…In another study, Ekesi (2020) analyzed the genomes of bacteria isolated from the lameness outbreak in boiler farms in Arkansas, USA (25). Simon and colleagues isolated several distinct bacterial species from chondronecrosis and osteomyelitis lesions.…”
Section: Lameness Due To Staphylococcus Aureus Infectionmentioning
confidence: 99%